IDEOLOGI PANCASILA SEBAGAI DASAR MEMBANGUN NEGARA HUKUM DAN IMPLEMNTASI DI ERA REFORMASI INDONESIA - Syahlan Lamporo; Adit Saputra; Ryan Dirgantara; Jabar Anurantha Djafaara; Muh. Ma’ruf Ramadhan (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2026)
This study aims to analyze Pancasila ideology as the foundation for establishing the concept of a state based on law in Indonesia and its implementation in the reform era. Indonesia, as a constitutional state as stipulated in Article 1 paragraph (3) of the 1945 Constitution, possesses characteristics that differ from the concepts of rechtsstaat and rule of law in Western countries. These differences are influenced by Indonesia’s historical, ideological, social, and cultural background. The Indonesian rule of law did not emerge from resistance against absolutism, but rather from the spirit of independence and the noble values embodied in Pancasila. This research employs a doctrinal legal research method with a statute approach, using primary legal materials such as Pancasila and the 1945 Constitution, as well as relevant secondary literature. The findings indicate that the Indonesian legal state is fundamentally a Pancasila-based rule of law, integrating the principles of supremacy of law, equality before the law, and protection of human rights with the values of divinity, humanity, unity, democracy, and social justice. The implementation of Pancasila in the reform era must be reflected in development paradigms in the fields of law, politics, education, ideology, and national resilience to achieve justice and public welfare.